2001
DOI: 10.1081/cbi-100103963
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase I: Another Cog in the Circadian Clockworks

Abstract: Multiple components of the circadian central clock are phosphoproteins, and it has become increasingly clear that posttranslational modification is an important regulator of circadian rhythm in diverse organisms, from dinoflagellates to humans. Genetic studies in Drosophila have identified double-time (dbt), a serine/threonine protein kinase that is highly homologous to human casein kinase I epsilon (CKIepsilon), as the first kinase linked to behavioral rhythms. Identification of a missense mutation in CKIepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 33 publications
1
52
0
Order By: Relevance
“…Rhythmic post-translational modifications of clock proteins, including phosphorylation of the PER-CRY complex by casein kinase 1 ε/δ (CKIε/δ) ( Fig. 1), introduces temporal delays that contribute to the 24 h period of the clock [37]. At the cellular level, the clock influences, and is influenced by, circadian rhythms in metabolism; daily variations in glucose uptake and metabolism influence the clock through metabolic sensors, such as adenosine monophosphate-activated protein kinase (AMPK) [38].…”
Section: The Internal Timing System and Metabolic Dysfunctionmentioning
confidence: 99%
“…Rhythmic post-translational modifications of clock proteins, including phosphorylation of the PER-CRY complex by casein kinase 1 ε/δ (CKIε/δ) ( Fig. 1), introduces temporal delays that contribute to the 24 h period of the clock [37]. At the cellular level, the clock influences, and is influenced by, circadian rhythms in metabolism; daily variations in glucose uptake and metabolism influence the clock through metabolic sensors, such as adenosine monophosphate-activated protein kinase (AMPK) [38].…”
Section: The Internal Timing System and Metabolic Dysfunctionmentioning
confidence: 99%
“…the target site, presumably because of interactions with the positively charged arginine at the CKI position 178 (10,13). However, these in vitro sites are nonconserved even between mammalian PER2s, strongly suggesting that they are irrelevant to cellular PER2 phosphorylation and function.…”
Section: Discussionmentioning
confidence: 99%
“…When tested in vitro on multiple substrates, CKI tau was shown to have a much reduced overall catalytic activity (10,12,13). This partial loss-of-function mutation and its phenotype have been difficult to reconcile with our current understanding of the molecular feedback loop that governs timing in mammalian cells (13) and recent empirical observations on clock function (14)(15)(16). For example, Dey et al (15) reported that PER proteins disappeared from the nucleus more rapidly in the tau hamster than in WT controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). Posttranslational mechanisms such as protein phosphorylation of negative (PER and CRY [22][23][24] ) and positive (CLOCK and BMAL1 25,26 ) components also play important roles in core clock activity.…”
Section: Circadian Clocks-a Universal Timing Mechanism Controlling Rementioning
confidence: 99%